I who have never known men eaudiobook - Harpman, Jacqueline (Echo Point Books & Media, LLC, 2024)
Deep underground, 39 women live imprisoned in a cage. Watched over by guards, the women have no memory of how they got there, no notion of time, and only a vague recollection of their lives before. As the burn of electric light merges day into night and numberless years pass, a young girl—the 40th prisoner—sits alone and outcast in the corner. Soon she will show herself to be the key to the others' escape and survival in the strange world that awaits them above ground. Informed by her background as a psychoanalyst and her youth in exile, I Who Have Never Known Men is a haunting, heartbreaking post-apocalyptic novel of female friendship and intimacy, and the lengths people will go to maintain their humanity in the face of devastation. Back in print for the first time since 1997, Jacqueline Harpman's modern classic is an important addition to the growing canon of feminist speculative literature. This audio edition of I Who Have Never Known Men is expertly read by Nikki Massoud, a listener favorite. Produced and published by Echo Point Books & Media, an independent bookseller in Brattleboro, Vermont. ©1997, 2019 Ros Schwartz.